Assessment of the Vertical Dimension of Occlusion Using Palm Width and Finger Length - Cecilia Bacali; Mariana Constantiniuc; Antarinia Craciun; Daniela Popa (Medicina)
Background and Objectives: The vertical dimension of occlusion’s (VDO) assessment is a highly important issue in the everyday dentist’s practice. Patients with unstable occlusion, lost occlusal stops, extensive tooth loss in the lateral area, or complete edentulism need a proper assessment of the VDO before the prosthetic restoration is carried out. Subjective and objective methods were used over time for the restoration of VDO. The study aimed to investigate the possible correlation between finger length, palm width and the vertical dimension of occlusion. Materials and Methods: Assessment of the VDO for 236 subjects, Romanian and French dental students, was performed using the Willis Bite Gauge. The left hand of the subjects was scanned using a flat-bed scanner, and then measurements of palm width and finger length were carried out for each subject. Comparison between VDO values and finger length/palm width was conducted using one-way ANOVA and Student t-Test. Results: Higher VDO average values were found in French subjects compared with Romanian students. The same results were found according to gender; in both female and male subjects, lower values of VDO were found in the Romanian group. Higher values were obtained for women within each group when comparing to men. Statistically significant correlations of the analyzed parameters and VDO values were found. Higher statistical correlations of the studied variables were found for men compared to women in both groups. The highest statistical correlation was obtained between the VDO and the palm width measured at the fingerbase, followed by the middle finger length. Conclusions: The results showed the highest statistical correlation between the vertical dimension of occlusion and the palm width measured at the fingers’ base. Statistical correlations were also found between the VDO and the middle finger length. Simple formulas using finger length/palm width can be used for a rapid VDO determination.